Government spending policies to promote economic growth and reduce poverty in developing countries: A study in North Maluku, Indonesia - Prince Charles Heston Runtunuwu; Hanafi Hussin (Trigin Publisher, 2025)
Government spending plays a vital role in promoting economic growth and reducing poverty, especially in developing regions. In Indonesia, fiscal policies are a key instrument for achieving equitable development across provinces. North Maluku, one of Indonesia’s less-developed regions, faces persistent challenges in infrastructure, education, healthcare, and income inequality. Examining how government spending is allocated and its effectiveness in stimulating economic activity provides valuable insights into policy performance. This study explores the relationship between government expenditure, economic growth, and poverty reduction in North Maluku, aiming to identify which spending components most effectively enhance welfare and sustainable regional development. The objective of this study is to examine the financial performance of the Ternate Islands City government and to determine how this performance influences both economic growth and the open unemployment rate in the region. The analysis is based on quantitative data obtained from various sources, including reports on the realization of the Regional Revenue and Expenditure Budget (APBD), economic growth statistics, and data on the open unemployment rate of Ternate Islands City. All secondary data were collected from the Regional Development Planning Agency (Bappeda), the Central Statistics Agency (BPS), and other relevant official reports. This study employs time series data covering the period from 2015 to 2022 and applies path analysis to evaluate the relationships among variables. The main variables analyzed include regional financial performance, economic growth, and unemployment levels. The findings reveal that the local government’s financial performance measured through indicators of independence, efficiency, effectiveness, and expenditure alignment has a significant impact on economic growth.